The orientalization of gender - Hasan, Md. Mahmudul (The International Institute of Islamic Thought, 2005)
Said’s critique of Orientalism provokes a comprehensive review by post-colonial theorists of the bulk of western knowledge regarding non-western countries. This Orientalist literature buttresses the colonial notion of a civilizing mission, which is also supported by many western feminists who provide theoretical grounds to such colonialist perceptions. Such post-colonial feminists as Gayatri Spivak, Chandra Mohanty, and Rajeswari Rajan analyze western feminism’s ideological complicity with Orientalist and imperialist ventures.